Magnetic Tweezers‐Based 3D Microchannel Electroporation for High‐Throughput Gene Transfection in Living Cells. Issue 15 (2nd December 2014) - Chang, Lingqian; Howdyshell, Marci; Liao, Wei‐Ching; Chiang, Chi‐Ling; Gallego‐Perez, Daniel; Yang, Zhaogang; Lu, Wu; Byrd, John C.; Muthusamy, Natarajan; Lee, L. James; Sooryakumar, Ratnasingham
<x xml:space="preserve">Abstract</x> A novel high‐throughput magnetic tweezers‐based 3D microchannel electroporation system capable of transfecting 40 000 cells/cm2 on a single chip for gene therapy, regenerative medicine, and intracellular detection of target mRNA for screening cellular heterogeneity is reported. A single cell or an ordered array of individual cells are remotely guided by programmable magnetic fields to poration sites with high (>90%) cell alignment efficiency to enable various transfection reagents to be delivered simultaneously into the cells. The present technique, in contrast to the conventional vacuum‐based approach, is significantly gentler on the cellular membrane yielding >90% cell viability and, moreover, allows transfected cells to be transported for further analysis. Illustrating the versatility of the system, the GATA2 molecular beacon is delivered into leukemia cells to detect the regulation level of the GATA2 gene that is associated with the initiation of leukemia. The uniform delivery and a sharp contrast of fluorescence intensity between GATA2 positive and negative cells demonstrate key aspects of the platform for gene transfer, screening and detection of targeted intracellular markers in living cells.